Interatomic push-pull engineering in heterocyclic covalent organic frameworks for boosting photocatalytic hydrogen peroxide production - Wenjun Yang; Jialong Lv; Yuelin Chen; Weikang Peng; Shibin Zheng; Wei Lin; Jinhong Bi; Guocheng Huang (Chemical Engineering Journal, 2026)

Origins of Miocene basaltic magmatism in the western Yarlung-Tsangpo Suture Zone, southern Tibet: Insight into the lateral and longitudinal tearing of the subducted Indian continental slab - Jianbo Cheng; Xianshu Dong; Yalin Li; Shuai Li; Siqi Xiao; Wenjun Bi; Rui Zhou (Chemical Geology, 2026)

Dynamic changes and functional analysis of the vaginal microbial communities in reproductively dysfunctional giant pandas - Xin Chen; Ling Dao; Wenjun Huang; Bi Li; Xiaolan Wang; Zhengyu Chen; Fangfang Liu; Li Luo; Fan Xu (The Veterinary Journal, 2026)

New application of Papiliotrema aurea: Isolation, biocontrol of postharvest green mold in citrus and antagonistic mechanisms - Tong Li; Bi Liao; Wenjun Wang; Lili Deng; Jian Ming; Kaifang Zeng (Postharvest Biology and Technology, 2026)

Quantitative fluvial geomorphological constraints on differential activity of boundary faults and phased uplift of the Bogda Mountains in the northern Tian Shan, NW China - Jiaoyan Yang; Dongli Zhang; Qi Su; Haiyun Bi; Yige Li; Fuer Yang; Wenjun Zheng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Identification of the North Jining Basin Fault and its response to the northward expansion of the Shanxi rift system, North China - Zhikang Gong; Dongli Zhang; Weisheng Hou; Ting Liu; Jinhua Du; Haoyu Zhou; Zijian Feng; Xin Sun; Ruijie Xue; Haiyun Bi; Wenjun Zheng (Tectonophysics, 2026)

A central Tibetan highland during the Late Jurassic: Insights from sedimentology, provenance and detrital zircon trace element of the Xueshan Formation in the Qiangtang Basin - Jiawei Zhang; Zhongpeng Han; Yalin Li; Jiarun Tu; Jingen Dai; Xingduo Ma; Zijian Li; Zhihao He; Shuai Li; Wenjun Bi (Global and Planetary Change, 2026)

Paleocene to Eocene deformation and crustal shortening history of the Tanggula Range, Central Tibet - Wenjun Bi; Yalin Li; Zhongpeng Han; Chengshan Wang; Jiawei Zhang; Tiankun Xu; Dawei Lv; Chan Wang; Zining Ma; Haiyang He; Huan Chen (Global and Planetary Change, 2026)

Miocene N-MORB- and OIB-type diabase dikes in the western Yarlung Tsangpo suture zone, southern Tibet: Insights into the Indian slab tearing and asthenosphere–lithosphere interaction - Jianbo Cheng; Yalin Li; Xianshu Dong; Siqi Xiao; Shuai Li; Wenjun Bi; Rui Zhou (Lithos, 2025)

MWCNT-OH/PDMS elastomer-based microwave absorber with high-performance thermal stability and mechanical sensing properties - Jialiang Chen; Kaixi Bi; Shuqi Han; Hao Liu; Wenjun He; Yifan Li; Guangchen Yin; Wenqi Xiong; Linyu Mei; Xiujian Chou (Chemical Engineering Journal, 2025)

Engineering intermolecular C–F···C=O interactions in covalent organic framework promotes dual-path H2O2 photosynthesis for sustainable disinfection - Yuxin He; Guocheng Huang; Xuejian Guo; Shaokui Chen; Qiaoshan Chen; Wenjun Yang; Weikang Peng; Xiaoying Xu; Jie Ye; Jinhong Bi; Po Keung Wong (Water Research, 2025)

Paleoearthquake sequence in the eastern segment of the Serteng Shan frontal fault (Hetao graben, North China) during the last 50 ka - Xin Sun; Yanxiu Shao; Wenjun Zheng; Dongli Zhang; Haiyun Bi; Jinhua Du (Tectonophysics, 2025)

Discrimination of tea varieties and bud sprouting phenology using UAV-based RGB and multispectral images - Litao Sun; Jiazhi Shen; Yilin Mao; Xiaojiang Li; Kai Fan; Wenjun Qian; Yu Wang; Caihong Bi; Hui Wang; Yang Xu; Jingbiao Xu; Zhaotang Ding (International Journal of Remote Sensing, 2025)

Probabilistic evaluation of enterprises' fraudulent report in pollutant levels based on machine learning: a case of hazardous waste generation quantity - Wen Fang; Qingyuan Yu; Wenjun Xie; Jianxun Yang; Zongwei Ma; Miaomiao Liu; Jun Bi (Resources, Conservation and Recycling, 2025)

The cell death-inducing protein BcPlp1 from Botrytis cinerea contributes to pathogenicity and modulates plant resistance - Xiaofei Nie; Ziyao Wang; Binbin Huang; Qiongnan Gu; Ran Xu; Shuang Yu; Chao Xiong; Zhiguo Liu; Wei Wei; Kai Bi; Wenjun Zhu (Plant Science, 2025)

Cloning and characterization of one novel PR1 gene from Coptis chinensis responding to southern blight - Ran Xu; Xiaohan Li; Yue Ming; Bo Wang; Kai Bi; Limei Wang; Hongxun Wang; Wenjun Zhu; Jingmao You (Physiological and Molecular Plant Pathology, 2025)

Implications of the different submerged extent of typical sandbars to local DOM and SDOM during the pre-flood season in the middle reaches of Yangtze River - Haoyang Shi; Hui Guo; Wenjun Yang; Chengcheng Bao; Xinxin Zhu; Sheng Bi; Yu Hu; Ting Li (Journal of Environmental Management, 2025)

Seismic activity characteristics of the Tongkuang Shan fault (Southeastern Tian Shan, China) revealed by high-resolution topographic data - Hui Qiu; Haiyun Bi; Wenjun Zheng; Jiangyuan Zeng; Bingxu Liu; Shiqi Wei (Journal of Asian Earth Sciences, 2025)

Polypyrrole-mediated construction of superhydrophobic photo/electro thermal composite fabric for efficient crude oil dehydration and recovery - Yihao Guan; Wenjun Zhang; Bingqian Bi; Sijing Cao; Zhining Wang; Hongbo Zeng; Yiming Li (Desalination, 2024)

Creep mechanism of landslide formation in rock with bedding and weak layers in Zezhou, Shanxi, China - Zhiqiang Yi; Jianhui Long; Wenhui Shi; Hongyan Yan; Jining Zhang; Wenjun Bi; Yuqi Jin (Bulletin of Engineering Geology and the Environment, 2024)

Allergenicity risk in animal-based food proteins: Source, dietary factors effect, allergen detection and processing modification methods - Yanxiang Bi; Changqi Liu; Fei Pan; Wenjun Peng; Xiaoming Fang; Huilian Che; Wenli Tian (Trends in Food Science & Technology, 2024)

Late Triassic paleolatitude of the Southern Qiangtang terrane, central Tibet: Implications for the closure of the Longmu Co-Shuanghu Paleo-Tethyan Ocean - Xingduo Ma; Yalin Li; Xiaodong Tan; Shuai Li; Zijian Li; Jiawei Zhang; Wenjun Bi; Yongyong Jia; Bo Yang (Journal of Asian Earth Sciences, 2024)

Zygotic quiescence prolongs the reproductive cycle in Berchemia sinica (Rhamnaceae) - Fang Ma; Yaolei Fu; Wenjun Wei; Ziwei Li; Jing Liu; Baoxia Bi; Wenzhe Liu (Flora, 2024)

Fault slip behavior and segmentation revealed by geomorphic offset clusters: An example from the middle Riganpei Co fault, central Tibet - Qing Tang; Wenjun Zheng; Haiyun Bi; Dongli Zhang; Bingxu Liu; Shiqi Wei (Journal of Asian Earth Sciences, 2024)

New paleoseismic events reveal decamillenial recurrence time for large earthquakes (M ≥ 7) along the Yuguang Graben Fault in North China - Hui Peng; Wenjun Zheng; Shaopeng Dong; Qiyun Lei; Haiyun Bi; Xulong Wang; Dongli Zhang; Xinnan Li; Zhikang Gong; Jinhua Du (Tectonophysics, 2023)

Quantifying seasonal ground deformation in Taiyuan basin, China, by Sentinel-1 InSAR time series analysis - Wei Tang; Xiangjun Zhao; Gang Bi; Mingjie Chen; Siyu Cheng; Mingsheng Liao; Wenjun Yu (Journal of Hydrology, 2023)

Comprehensive Analysis of Aldehyde Dehydrogenases (ALDHs) and Its Significant Role in Hepatocellular Carcinoma - Senbang Yao; Wenjun Chen; He Zuo; Ziran Bi; Xiuqing Zhang; Lulian Pang; Yanyan Jing; Xiangxiang Yin; Huaidong Cheng (Biochemical Genetics, 2022)
Oxidative DNA damage is closely related to the occurrence and progression of cancer. Oxidative stress plays an important role in alcohol-induced hepatocellular carcinoma (HCC). Aldehyde dehydrogenase (ALDH) is a family of enzymes that plays an essential role in the reducing oxidative damage. However, how ALDHs family affects alcohol-related HCC remains obscure. We aimed to explore the correlation between the differential expression of ALDHs in patients with HCC and pathological features, as well as the relationship between ALDHs and prognosis, and finally analyze the possible mechanism of ALDHs in targeted therapy of HCC. The data of HCC were downloaded from The Cancer Genome Atlas (TCGA) database. This research explored the expression and prognostic values of ALDHs in HCC using Oncomine, UALCAN, Human Protein Atlas, cBioPortal, Kaplan–Meier plotter, GeneMANIA, Tumor Immune Estimation Resource, GEPIA databases, and WebGestalt. Low mRNA and protein expressions of ALDHs were found to be significantly associated with tumor grade and clinical cancer stages in HCC patients. In particular, the loss of ALDH expression is more obvious in Asians, and its effect on prognosis is far more significant than that in the White race. Our findings play an important role in the study of prognostic markers and anti-liver cancer therapeutic targets for the members of the ALDHs family, especially in patients with liver cancer in Asia.

Botrytis cinerea BcSSP2 protein is a late infection phase, cytotoxic effector - Wenjun Zhu; Mengxue Yu; Ran Xu; Kai Bi; Shuang Yu; Chao Xiong; Zhiguo Liu; Amir Sharon; Daohong Jiang; Mingde Wu; Qiongnan Gu; Ling Gong; et al. (Environmental Microbiology, 2022)
Summary Botrytis cinerea is a broad‐host‐range necrotrophic phytopathogen responsible for serious diseases in leading crops. To facilitate infection, B . cinerea secretes a large number of effectors that induce plant cell death. In screening secretome data of B . cinerea during infection stage, we identified a phytotoxic protein (BcSSP2) that can also induce immune resistance in plants. BcSSP2 is a small, cysteine‐rich protein without any known domains. Transient expression of BcSSP2 in leaves caused chlorosis that intensifies with time and eventually leads to death. Point mutations in eight of 10 cysteine residues abolished phytotoxicity, but residual toxic activity remained after heating treatment, suggesting contribution of unknown epitopes to protein phytotoxicity. The expression of bcssp2 was low during the first 36 h after inoculation and increased sharply upon transition to late infection stage. Deletion of bcssp2 did not cause statistically significant changes in lesions size on bean and tobacco leaves. Further analyses indicated that the phytotoxicity of BcSSP2 is negatively regulated by the receptor‐like kinases BAK1 and SOBIR1. Collectively, our findings show that BcSSP2 is an effector protein that toxifies the host cells, but is also recognized by the plant immune system.

Transition from oceanic subduction to continental collision in central Tibet: evidence from the Cretaceous magmatism in Qiangtang block - Haiyang He; Yalin Li; Zijie Ning; Chengshan Wang; Siqi Xiao; Wenjun Bi; Huanbao Zhang; Zhengqing Wang; Liang Chen (International Geology Review, 2022)

Deformation and cooling history of the Central Qiangtang terrane, Tibetan Plateau and its tectonic implications - Wenjun Bi; Zhongpeng Han; Yalin Li; Chengming Li; Chengshan Wang; Jiawei Zhang; Jianyun Han; Haiyang He; Xinyu Qian; Tiankun Xu; Zining Ma (International Geology Review, 2021)

Klotho recovery by genistein via promoter histone acetylation and DNA demethylation mitigates renal fibrosis in mice - Yanning Li; Fang Chen; Ai Wei; Fangfang Bi; Xiaobo Zhu; Shasha Yin; Wenjun Lin; Wangsen Cao (Journal of Molecular Medicine, 2019)

CASCIRE surveillance network and work on avian influenza viruses - Yuhai Bi; Weifeng Shi; Jianjun Chen; Quanjiao Chen; Zhenghai Ma; Gary Wong; Wenxia Tian; Renfu Yin; Guanghua Fu; Yongchun Yang; William J. Liu; Chuansong Quan; et al. (Science China Life Sciences, 2017)

Using an unmanned aerial vehicle for topography mapping of the fault zone based on structure from motion photogrammetry - Haiyun Bi; Wenjun Zheng; Zhikun Ren; Jiangyuan Zeng; Jingxing Yu (International Journal of Remote Sensing, 2017)

Characterization of avian paramyxovirus type 6 isolated from a Eurasian teal in the intersection of migratory flyways in Russia - Ivan A. Sobolev; Kirill Sharshov; Kseniya Yurchenko; Denis Korneev; Alexandra Glushchenko; Tatyana Alikina; Marsel Kabilov; Yuhai Bi; Wenjun Liu; Natalia Gubanova; Alexander Shestopalov (Archives of Virology, 2016)

Single-step concentration and purification of adenoviruses by coxsackievirus-adenovirus receptor-binding capture and elastin-like polypeptide-mediated precipitation - Qian Wu; Wenjun Liu; Bi Xu; Xinyu Zhang; Xiaoli Xia; Huaichang Sun (Archives of Virology, 2016)

Validity of the Rytov Approximation in the Form of Finite-Frequency Sensitivity Kernels - Wenjun Xu; Xiao-Bi Xie; Jianhua Geng (Pure and Applied Geophysics, 2015)

Development and application of a reverse transcription loop-mediated isothermal amplification method for rapid detection of Duck hepatitis A virus type 1 - Limin Yang; Jing Li; Yuhai Bi; Lei Xu; Wenjun Liu (Virus Genes, 2012)

Precise molybdenite Re–Os and mica Ar–Ar dating of the Mesozoic Yaogangxian tungsten deposit, central Nanling district, South China - Jiantang Peng; Mei-Fu Zhou; Ruizhong Hu; Nengping Shen; Shunda Yuan; Xianwu Bi; Andao Du; Wenjun Qu (Mineralium Deposita, 2006)